Ewing sarcoma/primitive neuroectodermal tumor with chondroid differentiation: a potential diagnostic pitfall - Mussi, Maria Carolina Martins; Pigatti, Fernanda Mombrini; Tobouti, Priscila Lie; Sedassar, Bruno Tavares; Pinto Junior, Decio dos-Santos; Sousa, Suzana Cantanhede Orsini Machado de (Journal of Oral Diagnosis, 2021)
Ewing sarcoma/Primitive neuroectodermal tumor (ES/PNET) with chondroid differen- tiation and mesenchymal chondrosarcoma (MSC) have similar histopathological features. It may be difficult to distinguish both lesions without genetic or molecular analysis. The main aim of this case report is to highlight the difficulty in establishing the diagnosis of ES/ PNET with areas of chondroid differentiation. A 14-year-old female patient with painful right mandibular swelling. Imaging exams showed an extensive osteolytic lesion with mineralized areas. Histomorphologic and immunohistochemistry studies were performed. In situ hybridization was necessary to confirm the diagnosis. Immunohistochemistry and H&E-stained sections did not provide sufficient evidence to differentiate ES/PNET from MCS. The genetic tool demonstrated EWS1 gene breakpoint. ES/PNET with chondroid differentiation is rare and new studies are necessary to standardize molecular biomarkers and/or the panel of antibodies required to differentiate ES/PNET from MCS.